Workplace Violence and Neurosurgical Practice: Insights From the Council of State Neurosurgical Societies Workplace Violence Survey. (1st September 2019) - Schmidt, Tyler; Tomlinson, Samuel; Kimmell, Kristopher T; Rosenow, Joshua M; Phelps, Jeremy T
Abstract: INTRODUCTION: Workplace violence is a challenge that exists in neurosurgical practice. The emotional and intense nature of neurosurgical diseases is a risk factor for workplace violence which can manifest in many ways including verbal threats, physical assault, stalking, and other unwelcome confrontations. The scope of this issue in current neurosurgical practice is understudied. METHODS: A 26-item questionnaire assessing the experience of workplace violence was disseminated by the Council of State Neurosurgical Societies (CSNS) to neurosurgeon members of the American Association of Neurological Surgeons between August and December 2018. Descriptive statistics and fisher's exact tests were used to analyze responses. RESULTS: Respondents (N = 107) were predominately male (87%), and most had >20 yr of practice experience (63%). Most respondents practiced in urban (85%) and academic (60%) settings. Almost half of respondents (46%) reported fear of becoming a victim of workplace violence. 44% of respondents reported having received a verbal threat from a patient in the last 2 yr, and 41% reported receiving a verbal threat from a patient's family or friend. Stalking incidents (9%) and physical assault (3%) were also reported. Female neurosurgeons were more likely to receive verbal threats from patients ( P  = .04). As a direct result of perceived threat, 10% of respondents obtained a gun and/or a concealed weapon permit, which was more common among neurosurgeons in non-academic practice. Among those who experienced workplace violence, 47% accessed supportive resources on their own. CONCLUSION: Workplace violence is a growing concern in neurosurgical practice. Our survey found that the perceived fear of violence was high (46%), with 40% of respondents feeling less safe in the workplace today than when they began practice. These issues disproportionately impacted female neurosurgeons. The results of this survey indicate a need for more study and better educational resources to combat this issue.